A PERSONALIZED APPROACH TO THE STUDY OF THE PROBLEM OF EDUCATIONAL AND PEDAGOGICAL FORECASTING IN UKRAINE IN THE EARLY TWENTIETH CENTURY - Cherniak S. G. (International Journal of Innovative Technologies in Social Science, 2020)
The article is devoted to the study of a personalized approach to the problem of educational and pedagogical forecasting in Ukraine in the early twentieth century. The author emphasizes that a personalized approach to the study of the problem of educational and pedagogical forecasting in the early twentieth century is the main prerequisite for the development of forecasting pedagogical thought, which must be specified. I.Ya. Franco saw the direction of educational influence in the mastery of scientific knowledge, the harmonious improvement of the body in the process of physical labor. S.F. Rusova, as the coryphaeus of preschool pedagogy, laid the foundation for the content of the educational process through the introduction of the native language, national holidays, and Christian values of the Ukrainian people. G.G. Vashchenko took the Christian ideal as the basis for predicting pedagogical phenomena and processes. P.P. Blonsky defended the independent nature of pedagogical science. І.І. Ogienko stressed the importance of native education, the formation of Christian virtue, justice, and diligence. B.D. Grinchenko defended the inseparable connection of education with the life and culture of other peoples. L. Ukrainka had the same opinion. The teacher insisted on the importance of considering the role of the teacher in the public school, sharply raised the issue of the struggle for social and national liberation of the Ukrainian people. T.G. Lubnets is considered the luminary of the theory of pedagogy. H.D. Alchevskaya entered the history of pedagogy in Ukraine as a prominent figure in the field of adult education, organizer of Sunday schools. І.М. Steshenko advocated the nationalization of secondary and higher education. Minister P.M. Ignatiev defined the organizational and pedagogical principles of educational and pedagogical forecasting through the reform of the education system.